Observation on the Foraging Activities of Carpenter Ants in Secondary Forest in UNIMAS Campus - Augusta Rose Bano, Richard Riti (Universiti Malaysia Sarawak (UNIMAS), 2022)
This study attempts to gather more information on the foraging activity and the food preferences based on nutrients specific to carpenter ants Camponotus sp., in a secondary lowland forest, UNIMAS campus. The foraging activity of Camponotus sp. workers was examined by conducting observations on the ant activity as well as the food input. The experiment on food preferences of Camponotus sp. used the baited method with two different types of nutrient content: honey and canned tuna, throughout the foraging trail and determining which food is the most preferred. The results of this study show that Camponotus sp. is a nocturnal forager. Although it was observed that Camponotus sp. is an opportunist species, they preferred high levels of sugar compared to high protein. During the experiment, other ant species, notably Solenopsis sp., Dolichoderus sp., Pheidologeton affinis and Camponotus gigas, managed to monopolise the non-exploit baits left by Camponotus sp.. This study enhanced our knowledge on the food resource exploitation of carpenter ants in secondary forests, and provide useful information for ant control and pest management in the future.